Multiyear Survey of Coccidia, Cryptosporidia, Microsporidia, Histomona, and Hematozoa in Wild Quail in the Rolling Plains Ecoregion of Texas and Oklahoma, USA. (16th June 2016) - Xiang, Lixin; Guo, Fengguang; Yu, Yonglan; Parson, Lacy S.; LaCoste, Lloyd; Gibson, Anna; Presley, Steve M.; Peterson, Markus; Craig, Thomas M.; Rollins, Dale; Fedynich, Alan M.; Zhu, Guan
Abstract: We developed nested PCR protocols and performed a multiyear survey on the prevalence of several protozoan parasites in wild northern bobwhite ( Colinus virginianus ) and scaled quail ( Callipepla squamata ) in the Rolling Plains ecoregion of Texas and Oklahoma (i.e. fecal pellets, bird intestines and blood smears collected between 2010 and 2013). Coccidia, cryptosporidia, and microsporidia were detected in 46.2%, 11.7%, and 44.0% of the samples ( n = 687), whereas histomona and hematozoa were undetected. Coccidia consisted of one major and two minor Eimeria species. Cryptosporidia were represented by a major unknown Cryptosporidium species and Cryptosporidium baileyi . Detected microsporidia species were highly diverse, in which only 11% were native avian parasites including Encephalitozoon hellem and Encephalitozoon cuniculi, whereas 33% were closely related to species from insects (e.g. Antonospora, Liebermannia, and Sporanauta ). This survey suggests that coccidia infections are a significant risk factor in the health of wild quail while cryptosporidia and microsporidia may be much less significant than coccidiosis. In addition, the presence of E. hellem and E. cuniculi (known to cause opportunistic infections in humans) suggests that wild quail could serve as a reservoir for human microsporidian pathogens, and individuals with compromised or weakened immunity should probably take precautions while directly handling wild quail.